Tyrosine phosphorylation tunes chemical and thermal sensitivity of TRPV2 ion channel - Xiaoyi Mo; Peiyuan Pang; Yulin Wang; Dexiang Jiang; Mengyu Zhang; Yang Li; Peiyu Wang; Qizhi Geng; Chang Xie; Hai-Ning Du; Bo Zhong; Dongdong Li; et al. (eLife, 2022)
Transient receptor potential vanilloid 2 (TRPV2) is a multimodal ion channel implicated in diverse physiopathological processes. Its important involvement in immune responses has been suggested such as in the macrophages’ phagocytosis process. However, the endogenous signaling cascades controlling the gating of TRPV2 remain to be understood. Here, we report that enhancing tyrosine phosphorylation remarkably alters the chemical and thermal sensitivities of TRPV2 endogenously expressed in rat bone marrow-derived macrophages and dorsal root ganglia (DRG) neurons. We identify that the protein tyrosine kinase JAK1 mediates TRPV2 phosphorylation at the molecular sites Tyr(335), Tyr(471), and Tyr(525). JAK1 phosphorylation is required for maintaining TRPV2 activity and the phagocytic ability of macrophages. We further show that TRPV2 phosphorylation is dynamically balanced by protein tyrosine phosphatase non-receptor type 1 (PTPN1). PTPN1 inhibition increases TRPV2 phosphorylation, further reducing the activation temperature threshold. Our data thus unveil an intrinsic mechanism where the phosphorylation/dephosphorylation dynamic balance sets the basal chemical and thermal sensitivity of TRPV2. Targeting this pathway will aid therapeutic interventions in physiopathological contexts.